2012
DOI: 10.1681/asn.2011050472
|View full text |Cite
|
Sign up to set email alerts
|

Renal Leishmaniasis as Unusual Cause of Nephrotic Syndrome in an HIV Patient

Abstract: Renal involvement is a rare complication in HIV-1-infected patients leading to various pathologies and clinical symptoms. In addition to the classic HIV-1-associated nephropathy with collapsing-type focal segmental glomerulosclerosis and characteristic tubulocystic changes, which is more common in Afro-American than in Caucasian HIV-1 patients, immune complex GNs such as membranous GN and membranoproliferative GN are particularly common renal manifestations. Besides HIV-1 itself, a number of opportunistic infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…Histological findings reported in our series are in line with sporadic cases described in humans and in studies on dogs, where type III MPGN was the most commonpattern [15]-[22],[25],[26]. Interestingly, free Leishmania were observed inside the capillary lumen of two patients.…”
Section: Discussionsupporting
confidence: 90%
“…Histological findings reported in our series are in line with sporadic cases described in humans and in studies on dogs, where type III MPGN was the most commonpattern [15]-[22],[25],[26]. Interestingly, free Leishmania were observed inside the capillary lumen of two patients.…”
Section: Discussionsupporting
confidence: 90%
“…Several cases of amyloidosis in HIV infected IVDU have been described in the literature [5,6,13,14,16,17]. Besides IVDU, renal amyloidosis in HIV infected patients has been described in association with visceral leishmaniosis or multicentric Castleman`s disease [18-21], which were both not found in our cohort. During the same time period of this retrospective study, 25 HIV-infected patients without a history of IVDU underwent renal biopsy at our institutions and none of them had evidence of renal AA-amyloidosis [data not shown].…”
Section: Discussionmentioning
confidence: 48%
“…Urine is another source for detection of L. siamensis DNA. Although there are several reports of renal involvement in patients with leishmaniasis, 12,[25][26][27] the six patients had no evidence of renal disease. DNA extraction from urine requires 30 mL of urine, and we found that 50% of the patients in our series were negative for Leishmania DNA yet positive for DNA in saliva.…”
mentioning
confidence: 72%